(untitled) (London Journal of Engineering Research, 2024)
The present work deals with the use of the mandacaru cactus as an adsorbent material for the process of adsorption of the methylene blue dye present in wastewater, since this is an agricultural material of little applicability, used mainly in animal feed. In this sense, the mandacaru cactus was previously treated and applied in the process of removing this dye, evaluating the effects of the initial concentration of the pollutant, dosage of the adsorbent and adsorbent/adsorbate contact time. Furthermore, the adsorption mechanism was further studied by applying the pseudo-first and pseudo-second order models to the data obtained from the contact time parameter. The entire process was evaluated using UV-vis spectrophotometry as an analysis technique. The results obtained showed a maximum adsorption capacity of 36.18 mg/g, with a removal rate greater than 90%, presenting a mostly chemical process.